Public administration and public affairs - Henry, Nicholas (Englewood Cliffs, N.J. : Prentice-Hall, 1980)
In this second edition, a new introductory chapter confronts the underlying reasons for the growing popular hostility toward government and the rising autonomy of the public bureaucracy. A new chapter on program evaluation has been added. The chapters on Public Personnel Administration, Budgeting, Federalism, and Urbanism have been so extensively reformulated that they too are new. The section on Organization theory has been refined. In short, the second edition is designed to be useful as well as educational.
Includes bibliographical references and index.
ne 11/07/2018
Loans
Keywords: Public administration